2013
DOI: 10.1117/1.oe.52.5.055008
|View full text |Cite
|
Sign up to set email alerts
|

Optical key distribution system using atmospheric turbulence as the randomness generating function: classical optical protocol for information assurance

Abstract: Abstract. We describe an experimental laboratory system that generates and distributes random binary sequence bit streams between two optical terminals (labeled Alice and Bob). The random binary sequence is generated through probing the optical channel of a turbulent atmosphere between the two terminals with coincident laser beams. The two laser beams experience differential phase delays while propagating through the atmospheric optical channel. The differential phase delays are detected and sampled at each te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The detectors are InGaAs transimpedance amplified photodetectors (PDAs) from Thorlabs. The introduction of a temporal phase modulation, or dither signal, on the reference arm of the interferometer was critical for precise calculations of the phase distortions [4,16]. We selected a frequency of 500 Hz, which was arbitrary.…”
Section: Experimental Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The detectors are InGaAs transimpedance amplified photodetectors (PDAs) from Thorlabs. The introduction of a temporal phase modulation, or dither signal, on the reference arm of the interferometer was critical for precise calculations of the phase distortions [4,16]. We selected a frequency of 500 Hz, which was arbitrary.…”
Section: Experimental Approachmentioning
confidence: 99%
“…It also provides an experimental validation for other works that suggest the use of the atmosphere as a random number generator (RNG); see Ref. [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that interferometric methods can be used to estimate the phase [7][8][9][10][11], with several practical applications [12][13][14][15]. Recently, the possibility of using the random phase acquired by a light field on propagation through atmospheric turbulence for cryptographic purposes has been explored [16][17][18]. In [16], random-key generation using phase fluctuations of a light field that has propagated through a turbulent atmosphere was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], random-key generation using phase fluctuations of a light field that has propagated through a turbulent atmosphere was demonstrated. In [17,18], it was shown that the phase acquired by a light field on propagation through atmosphericturbulence-like conditions can be used by two remote observers to distill a shared random key.…”
Section: Introductionmentioning
confidence: 99%